Microsoft Silverlight 3 [ a beginner's guide - Horn, Shannon (McGraw-Hill, 2010)
"Filled with hands-on examples Microsoft Silverlight 3: A Beginner's guide covers Visual Studio 2010 and the .NET Framework 4.0. Learn how to use Silverlight to stream multimedia content across the Web, develop dynamic, data-driven Silverlight applications, access data using XML and LINQ, and create XAML and WCF services. The book shows you how to test, debug, deploy, and secure your applications."--BOOK JACKET